The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.3109/17453674.2015.1113375
|View full text |Cite
|
Sign up to set email alerts
|

Epidural analgesia is superior to local infiltration analgesia in children with cerebral palsy undergoing unilateral hip reconstruction

Abstract: Background and purpose — Treatment of postoperative pain in children with cerebral palsy (CP) is a major challenge. We investigated the effect of epidural analgesia, high-volume local infiltration analgesia (LIA), and an approximated placebo control on early postoperative pain in children with CP who were undergoing unilateral hip reconstruction.Patients and methods — Between 2009 and 2014, we included 18 children with CP. The first part of the study was a randomized double-blind trial with allocation to eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 24 publications
(30 reference statements)
0
29
2
Order By: Relevance
“… 26 In Kjeldgaard Pedersen et al’s study, which tested the efficacy of epidural analgesia and local infiltration analgesia for early postoperative pain control in children undergoing unilateral hip reconstruction, the patients of the epidural group received continuous epidural infusion of local anesthetic during the anesthesia, which was maintained for the first 2–3 days postoperatively. 27 Although direct comparison is not possible, the postoperative r-FLACC pain scores in this study were rather slightly lower than in Kjeldgaard Pedersen et al’s study. Further controlled studies will be needed focusing on this issue.…”
Section: Discussioncontrasting
confidence: 67%
“… 26 In Kjeldgaard Pedersen et al’s study, which tested the efficacy of epidural analgesia and local infiltration analgesia for early postoperative pain control in children undergoing unilateral hip reconstruction, the patients of the epidural group received continuous epidural infusion of local anesthetic during the anesthesia, which was maintained for the first 2–3 days postoperatively. 27 Although direct comparison is not possible, the postoperative r-FLACC pain scores in this study were rather slightly lower than in Kjeldgaard Pedersen et al’s study. Further controlled studies will be needed focusing on this issue.…”
Section: Discussioncontrasting
confidence: 67%
“…Quality assessment of level I to level III studies found ( n =number of studies): strong ( n =2), moderate ( n =12), and weak ( n =8) quality. Adequate conduct and report of appropriate statistical evaluation including power evaluations was described in nine studies . Suitable methods for controlling confounding variables and limiting potential biases were not reported in any studies.…”
Section: Resultsmentioning
confidence: 99%
“…Management of postoperative pain was assessed after ( n =number of studies): lower limb orthopaedic surgery ( n =12) and selective dorsal rhizotomy surgery ( n =6) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When possible, regional analgesia should be performed to optimise postoperative pain management 3 . Continuous epidural catheterisation under general anaesthesia has been used to provide sufficient postoperative analgesia in the days following surgery 3,4 , and epidural analgesia is effective for postoperative pain control in paediatric patients [5][6][7][8] .…”
mentioning
confidence: 99%